Gray Love The Career of Gov. John Early in the Cordilleras - Woods, Shelton; Boise (Archīum Ateneo, 2013)
Unlike the usual portrayals of racism of American colonial officials in the Philippines, thisarticle explores the career of John Early, a mid-level official who rose to become the governor of the Mountain Province in 1922 until his death in 1932. In 1911 he had served as lieutenant governor of Bontoc but was fired, according to his memoir, for defending the rights of the indigenous highlanders against unfair American colonials. Early’s rather unorthodox rise in the colonial government included actions that at times appear to contradict the prevailing thoughts of the day. Thearticle asserts the complex nature of human motives.Keywords: American colonialism • Mountain Province • racism • Dean Worcester • Kalinga